DETERMINANTS OF PURCHASE INTENTION ON DONUTS INDUSTRY OF BRAND X IN JAKARTA - Karina, Karina; Ekawati , Sanny (International Journal of Application on Economics and Business, 2024)
This research is aimed to determine the influence of the e-WOM variables, perceived quality, and brand image on purchase intentions for brand X donut in Jakarta. The type of research design used in this research is descriptive with a cross-sectional data collection time method and a quantitative approach. Non-probability sampling with purposive sampling technique was used in this research. The instrument in this research uses a questionnaire in a Google form which is distributed online via social media such as WhatsApp, Line and Instagram. The population in this study were Jakarta residents who had bought this brand X donut. The sample size used in this research was 190 respondents. The data was analyzed using SmartPLS version 4 software application. Data analysis is divided into 2 (two), namely the outer and the inner model. The results of this research show that there is a positive but insignificant effect between e-WOM on purchase intentions. Perceived quality and brand image have a positive and significant influence on purchasing intentions. The benefit of this research is to provide input for brand X donut regarding the importance of maintaining quality and developing brand image in encouraging consumer purchasing intentions.